Selective Ablation of GABA Neurons in the Ventral Tegmental Area Increases Spontaneous Locomotor Activity. - Shank, Erik J.; Seitz, Patricia K.; Bubar, Marcy J.; Stutz, Sonja J.; Cunningham, Kathryn A. (Behavioral Neuroscience, 2007)
γ-aminobutyric acid (GABA) neurons in the ventral tegmental area (VTA) provide innervation to cortical and subcortical regions of the brain. To solidify the importance of these VTA GABA neurons in behavioral function, we employed the neurotoxin dermorphin-saporin (DS) to selectively lesion VTA GABA neurons prior to assessing spontaneous motor activity. Rats were bilaterally microinfused with DS (1.0 or 2.0 pmol/200 nl/side) or blank-saporin control (BS, 200 nl/side) into the VTA. Seven days later, DS-treated rats exhibited significantly elevated motility in comparison with BS-treated rats; this elevated motility normalized by Day 14 following pretreatment with 1.0 pmol of DS but was sustained on Day 14 after pretreatment with 2.0 pmol of DS. A selective loss of VTA GABA neurons on Day 14 was demonstrated through reduced expression of mRNA for glutamic acid decarboxylase-67 and (μ-opioid receptor, but not tyrosine hydroxylase (a dopamine neuron marker), in the VTA. Thus, a dose- and time-related selective loss of VTA GABA neurons was accomplished using this novel neurotoxin. This loss of GABA VTA neurons was associated with hypermotility, further supporting their important regulatory role in the generation of behavior. Reprinted by permission of the publisher.